Congenital hemihypertrophy with hemihypertrichosis - Akarsu, S; Coskun, BK; Aydin, AM; Tekatli, M; Aygun, AD (Japanese Dermatolgical Assoc, 2005)
The rare condition in which one side of the body seems to grow faster than the other is called hemihypertrophy. This may be accepted as normal, but there are certain serious conditions that may be associated with this type of growth pattern. Congenital hypertrichosis is believed to be a genetic disorder that is inherited or occurs as a result of spontaneous mutation. The incidence of generalised congenital hypertrichosis is about one in a billion. A seven-month-old female case was brought to the hospital with growth and hairiness complaints, which were more apparent in the right side of the face, the right arm and the right leg. Physical examination showed more apparent hypertrophy and hypertrichosis, which covered the entire right side of the body beginning from the face and including the lower extremities and the genitalia. Hypertrichosis was more evident above the right scapula and on the right leg. The diameter of the right upper extremity and the right lower extremity were measured at 13 mm and 14 mm thicker than the left side, respectively. The infant did not have teeth yet and had totally normal nail growth. Skeletal structure, cardiovascular, respiratory, urogenital, central nervous system and eye examinations were all normal. Results of all laboratory analyses, including genetic examination, and those of the imaging techniques were found to be normal. We hereby present the rare co-presence of hemihyertrophy and hemihypertrichosis, for which we could not identify an etiological cause and which is the third such case in the literature.
Keywords: hemihypertrophy; hypertrichosis; congenital